The The Aspects of Locality in Tafsir Kediri by Abdur Rohman: Analysis of Q.S. Al-Baqarah [2]: 67-73 About Slaughtering Female Cows - Wildah Nurul Islami; Fuady Fuady (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
Tafsir Kediri is one of the works of an Indonesian mufasir, and it has prominent characteristics in aspects of the Javanese locality, especially Kediri. Among the verses of the Qur'an that are interpreted based on locality within the scope of Abdur Rohman as a Kediri community can be seen in the interpretation of Q.S. Al-Baqarah [2]: 67-73. This verse tells the origin of the slaughter of female cows in the story of the Prophet Musa (AS). Using a qualitative approach, data were collected through interviews with the authors of Tafsir Kediri and an analysis of interpreters' interpretations regarding the focus of this paper's discussion. The research results show the answer to the problem formulation, namely, how the portrait of Tafsir Kediri by Abdur Rohman and the locality aspect in Abdur Rohman's interpretation of Q.S. al-Baqarah [2]: 67-73 concerning the slaughter of female cattle. From the results of the descriptive analysis, it was found that first, when interpreting Q.S. al-Baqarah [2]: 68, through the mention of the classification of cow names based on their age and the mention of Javanese editorials (including Kediri). Second, the locality aspect appears in the interpretation of Q.S. al-Baqarah [2]: 69 by mentioning a typical Javanese cow's color. Third, the locality aspect appears in the interpretation of Q.S. al-Baqarah [2]: 71 through the mention of Javanese terms for plowing rice fields. Mluku rice fields loosen the soil before planting and sowing seeds, while nggaru rice fields are the process of smoothing and leveling the land that has been mluku.